Content Analysis of Online Media Reporting on Environmental Issues of PT Semen Tonasa Company - Jerrynindra, Mohammad; Yusmanizar, Yusmanizar; Sukmarini, Andi Vita (Journal La Sociale, 2024)
Fajar.co.id's online media reporting regarding corporate environmental issues at PT Semen Tonasa has become an important concern in the midst of industrial activity, where the news is able to shape opinion in the community depending on how Fajar.co.id reviews news published to the public, there are tendencies of News is the cause of the formation of issues. To see whether Fajar.co.id tends to report positive or negative news, a content analysis of the news was carried out. This research uses a descriptive quantitative method, which is a method with an analytical approach that uses quantitative data to provide a description or description of the observed phenomena. This research focuses on how to determine the trend of reporting on news content related to environmental issues of the PT Semen Tonasa company through word-for-word analysis by a coder. by using the Scott formula to see the results and their explanation. The research data is primary data taken from the Fajar.co.id portal, namely news related to environmental issues of the PT Semen Tonasa company from 2019 to 2023, totaling 20 news articles. The research was carried out by analyzing the words made by a coder and then entering them into the Scott formula for get the trend value of positive or negative issues from the news. The results of the research showed that 85% of the reporting tended to be positive and 15% tended to be negative, where in conducting reporting, Fajar.co.id had shown good independence and was in line with ethics in the journalistic process.